Integrating environmental sustainability and project portfolio management: Case study in an energy firm - Jugend, Daniel [UNESP]; Figueiredo, José (FapUNIFESP (SciELO), 2017)
Although international and relevant research on environmental sustainability and project portfolio management is quite developed, there are few studies integrating the two areas. We could only identify research on each of the areas and very few interfaces between them, either in empirical or theoretical terms. In constructing a case study, our choice was to study of the existing European largest firms of energy production and supply, and one that is globally recognized in the area of renewable energy. This article aims to analyze and enable understanding of the policies and practices for integrating environmental sustainability and project portfolio management. Among the main results we observed that the environmental and social aspects of portfolio projects are inseparable for this organization. Good communication and active negotiation with stakeholders, especially with the local communities in the vicinity of projects, was highlighted as a management practice that may be used to improve project management performance. Furthermore, it was noted that logic in relation to identification, analysis and approval of new projects in the firm is also guided by the same environmental and social concerns.
Keywords: Environmental sustainability; Project management; Project portfolio management; Social sustainability